Theoretical and Experimental Investigation of Two-Phase Sub-Cooled Heat-Pipe at Different Regimes (Journal of Nuclear Technology in Applied Science, 2025)
The development of novel sub-cooled two-phase thermosyphon or heat-pipe devices is crucial for improving heat transfer efficiency. The properties are analyzed by the application of theoretical modeling and experimental observations of the sub-cooled heat loop during the heating-up, steady-state, and cooling-down stages. The heating rate effectiveness, cooling rate, and evaporator length of the sub-cooled heat-pipe are experimentally examined in the heating-up, steady-state, and cooling-down modes. The dynamic model of the sub-cooled heat-pipe is crucial for several applications including irregular operation in the current practical inquiry. The objective of this research is to develop a theoretical framework that appropriately models the dynamic features of the double-tube evaporator. This will be accomplished by analyzing several transient parameters during the warm-up, steady-state, and cool-down stages of operation. The model accurately replicates the phase and temperature characteristics of a sealed, sub-cooled heat-pipe that contains two distinct phases. The experimental results of the practical arrangement, which utilizes a thermal evaporator wall and a working fluid, exhibit a straightforward exponential pattern. The experimental measurements and theoretical model show a strong agreement.
Keywords: Heat-pipe; Sub cooled; Heat Pipe Simulation; transient; Steady-state